Aggregate fluctuations and the distribution of firm growth rates - Giulio Bottazzi; Le Li; Angelo Secchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
We propose an aggregate growth index that explicitly accounts for non-normality in the micro-economic distribution of firm growth rates and for the presence of a negative scaling relation between their volatility and the size of the firm. Using Compustat data on US publicly traded company, we show that the new index tracks aggregate fluctuations better than the sample average, confirming that the statistical properties characterizing the micro-economic dynamics of firms are relevant for the dynamics of the aggregate. To better characterize the origins of aggregate fluctuations, we decompose the index in two parts, describing respectively the modal (typical) value of growth rates and the tilt (asymmetry) of their distribution. Regression analysis shows that models based on this decomposition, despite their simplicity, possess a remarkable explanatory and predictive power with respect to the aggregate growth.
Keywords: C13; D22; E3; L25; 330; Firm growth rates asymmetry and volatility; Aggregate economic fluctuations and business cycles; Aggregation of non-normal variables